Implementasi Nilai-Nilai Syariah dalam Proses Produksi UMKM Tempe Kupas Kulit Mbah Anik di Kecamatan Medan Deli - Nadia Aswana; Nurly Aulia Rahman; Khasanah Khairiyyah; Pani Akhiruddin Siregar (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study discusses the implementation of Sharia values in the production process of the small-medium enterprise (SME) "Tempe Kupas Kulit Mbah Anik," a business established in 1978 on Jln. Mangaan 1 gg. Ali, owned by Siti Nurhayani with four employees. Sharia principles in business practices, such as honesty, cleanliness, and fairness, serve as essential foundations for managing a food-related business. This research aims to examine the application of Sharia values at every stage of production, from raw material selection and processing to product distribution. The study uses a qualitative approach, collecting data through interviews and direct observation. The findings reveal that Sharia values are consistently applied in the SME's production processes, particularly in the selection of halal, high-quality raw materials, maintaining cleanliness in production, and treating employees fairly. The implications of this study suggest that implementing Sharia principles in SMEs has the potential to enhance consumer trust and foster sustainable and ethical business development. This study is expected to inspire other SMEs to incorporate Sharia principles in their operational practices.